อิทธิพลของแรงดันนํ้าที่มีผลต่อการตัดอลูมิเนียมเกรด A1100 ในกระบวนการ ขึ้นรูปด้วยนํ้าแรงดันสูง The Influence of Water Pressure Affect Cutting for the Grade Aluminum A1100 in the Forming Process with High Pressure Water - สุขขี เมที; วิวัฒน์เจริญ ธวัช; มะธิโตปะนำ สุรศักดิ์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ การวิจัยนี้เป็นการศึกษาอิทธิพลของแรงดันนํ้าที่มีผลต่อความเรียบผิว และค่าความฉากของชิ้นงานของ วัสดุอลูมิเนียม A1100 โดยศึกษาแรงดันนํ้า 5 ระดับ คือ 170 200 240 275 และ 310 MPa ใช้ทราย เป็นสารขัดขนาด 120 Mesh ชิ้นงานทดลองมีลักษณะรูปสี่เหลี่ยมผืนผ้าขนาด 10 x 40 x 25 มิลลิเมตร ระยะยกหัวตัดจากชิ้นงานสูง 2.0 มิลลิเมตร อัตราการไหลของสารขัดอยู่ที่ 0.368 กิโลกรัมต่อนาที วิเคราะห์ข้อมูลทางสถิติด้วยเทคนิค ANOVA จากโปรแกรมคอมพิวเตอร์ ผลการศึกษาพบว่า แรงดันนํ้าที่เปลี่ยนแปลงส่งผลต่อความเรียบผิวรอยตัดของชิ้นงาน ซึ่งแรงดันนํ้า ที่เหมาะสำหรับการตัดวัสดุอะลูมิเนียมเกรด AA1100 คือ 170 MPa ได้ค่าความเรียบผิวดีสุด 2.53 ไมโครเมตร และให้ค่าความฉากของชิ้นงานดีสุด 0.59 องศา อีกทั้งยังพบว่าเมื่อแรงดันนํ้าเพิ่มขึ้น ทำให้ความเรียบผิว และค่าความฉากของชิ้นงานน้อยลง และยืนยันว่าแรงดันนํ้ามีอิทธิพลต่อความเรียบผิวและค่าความฉาก ของชิ้นงานที่ระดับนัยสำคัญ 0.05 Abstract This research was a study of the influences of water pressure affecting of surface roughness and perpendicular value of work pieces of Aluminum grade A1100 with 5 levels of water pressure as: 170, 200, 240, 275 and 310 MPa by using sand 120 Mesh as abrasives. The study was conducted on rectangular work pieces with dimension 10 x 40 x 25 mm, 2.0 mm. Stand - off distance and 0.368 kg/min of abrasive flow rate. ANOVA statistical method was used for analysis with a computer application. The results revealed that varied water pressures were affected to surface roughness. The proper water pressures for cutting Aluminum grade A1100 was at 170 MPa that yielded the best of average surface roughness at 2.53 m and the average perpendicular value of work pieces at 0.59 degrees. Moreover, it was also found that the more increased water pressure made more increased perpendicular value of work pieces and confirmed that water pressure influenced to the water pressure and perpendicular value of work pieces with statistically significant level of 0.05.